1998
DOI: 10.1029/98jd00900
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of aerosol properties from satellite measurements of backscattered ultraviolet radiation: Theoretical basis

Abstract: Abstract. We discuss the theoretical basis of a recently developed technique to characterize aerosols from space. We show that the interaction between aerosols and the strong molecular scattering in the near ultraviolet produces spectral variations of the backscattered radiances that can be used to separate aerosol absorption from scattering effects. This capability allows identification of several aerosol types, ranging from nonabsorbing sulfates to highly UV-absorbing mineral dust, over both land and water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
925
0
11

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 952 publications
(990 citation statements)
references
References 34 publications
27
925
0
11
Order By: Relevance
“…In previous aerosol retrieval studies with UV spectral region such as the Direct Method, the aerosol layer height used to be assumed as some constant values. However, a difference in aerosol layer height assignment by 1 km, possibly causes up to 70 % retrieval error in optical thickness (Torres et al 1998). Fortunately, we had a simultaneous LIDAR observation at the Shapotou site.…”
Section: Preliminary Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In previous aerosol retrieval studies with UV spectral region such as the Direct Method, the aerosol layer height used to be assumed as some constant values. However, a difference in aerosol layer height assignment by 1 km, possibly causes up to 70 % retrieval error in optical thickness (Torres et al 1998). Fortunately, we had a simultaneous LIDAR observation at the Shapotou site.…”
Section: Preliminary Results and Analysismentioning
confidence: 99%
“…Based upon the above residual method, Torres et al (1998) developed the Direct Method, so-called "the method retrieves optical thickness and single scattering albedo of UV-absorbing aerosols such as dust and soot". The method was applied to the TOMS long-term dataset (around 20 years) for semi-global analyses of aerosol optical thickness (Torres et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The TOMS project has produced the longest available global record of aerosol observations in terms of AI, and a number of studies have demonstrated its feasibility and success (e.g., Torres et al 1998;Chiappello et al 1999;Hsu et al 1999;Cakmur et al 2001;Prospero et al 2002;Duncan et al 2003). Monthly data on a 1.25°ϫ 1°grid are available on the TOMS Web site (http://toms.gsfc.nasa.gov/aerosols/aerosols_v8.html).…”
Section: Data and Analysismentioning
confidence: 99%
“…Recently, the Total Ozone Mapping Spectrometer (TOMS) instrument has been used for detecting absorbing aerosols based on the spectral contrast at 340 and 380 nm in the upwelling ultraviolet spectrum (13). TOMS is sensitive to UV-absorbing aerosols such as mineral dust, volcanic ash, and soot aerosol from fossil fuel combustion sources and biomass burning.…”
Section: The Global Scale Distribution Of Mineral Dustmentioning
confidence: 99%
“…Also, the AI is not a quantitative measure of aerosol concentration. TOMS is sensitive to a number of aerosol physical properties and, of most importance, to the altitude of the aerosols layer (13). Fig.…”
Section: The Global Scale Distribution Of Mineral Dustmentioning
confidence: 99%